2011
DOI: 10.1242/jeb.052993
|View full text |Cite
|
Sign up to set email alerts
|

Gliding saves time but not energy in Malayan colugos

Abstract: SUMMARY Gliding is thought to be an economical form of locomotion. However, few data on the climbing and gliding of free-ranging gliding mammals are available. This study employed an animal-borne three-dimensional acceleration data-logging system to collect continuous data on the climbing and gliding of free-ranging Malayan colugos, Galeopterus variegatus. We combined these movement data with empirical estimates of the metabolic costs to move horizontally or vertically to test this long-standing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
(51 reference statements)
1
32
0
Order By: Relevance
“…However, it should be remembered that such analyses have always been very challenging in free-ranging animals, and especially those that move over long periods and large spatial scales. Byrnes and colleagues (Byrnes et al, 2011), for example, effectively illustrated the power of ACC data recorded at 100Hz not only to identify climbing and gliding behaviors of free-ranging Malayan colugos, but also to quantify the climbing heights. However, such an application is naturally limited to relatively short times and small spatial scales, depends on physical retrieval of the data-loggers and requires complementary measurements of the horizontal component of movements.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be remembered that such analyses have always been very challenging in free-ranging animals, and especially those that move over long periods and large spatial scales. Byrnes and colleagues (Byrnes et al, 2011), for example, effectively illustrated the power of ACC data recorded at 100Hz not only to identify climbing and gliding behaviors of free-ranging Malayan colugos, but also to quantify the climbing heights. However, such an application is naturally limited to relatively short times and small spatial scales, depends on physical retrieval of the data-loggers and requires complementary measurements of the horizontal component of movements.…”
Section: Discussionmentioning
confidence: 99%
“…There have been two major efforts to record free-ranging gliders behaving under natural conditions. One on colugos used an accelerometer attached to the body to measure instantaneous acceleration throughout the glide (Byrnes et al 2011a, Byrnes et al 2008, Byrnes et al 2011b, and the other used high-speed cameras to track flying squirrels transiting to and from an artificial feeder ). Take-off has been examined in detail for snakes (Socha 2006) and mammals (Byrnes et al 2008, Essner 2002, Keith et al 2000, Paskins et al 2007) and landing has only been examined in mammals (Byrnes et al 2008, Paskins et al 2007).…”
Section: Terrestrial Vertebratesmentioning
confidence: 99%
“…Although many of the preceding scenarios have been noted in the literature, the ecological context of gliding has not been well quantified for most taxa, largely due to the logistical difficulty of tracking climbing and gliding animals (but see Byrnes et al 2011a, Byrnes et al 2008, Byrnes et al 2011b. The best understood systems are lizards of the genus Draco, mammalian colugos, and ants, which will be discussed in more detail in the taxon-specific sections.…”
Section: Introductionmentioning
confidence: 99%
“…Observations in Singapore showed that the diameter of trees used by colugos exceeded 45 cm (Byrnes et al 2008). Speed of vertical progression of colugos on tree trunks is about 1 m/s (Byrnes et al 2011).…”
Section: Climbing Up Trunksmentioning
confidence: 99%
“…Gliding leaps enable rapid movements for great distances and, even taking into account the time spent for climbing up the tree trunk, this locomotor pattern is more rapid than running from one tree to another along branches (Byrnes et al 2011). Moving by air between trees located at a considerable distance is not only faster, but also more economical and safer than running on the ground.…”
Section: Some Biological Aspects Of Colugos 207mentioning
confidence: 99%